A bibliometric analysis of self‐efficacy in low back pain from 1980 to 2021. Issue 4 (28th December 2022) - Wang, Zhe; Simon, Klára; Makai, Alexandra; Jaromi, Melinda
Abstract: Background: Self‐efficacy is one of the important factors affecting chronic diseases. In the current epidemiological context of low back pain (LBP), LBP self‐efficacy has become a topic of great practical interest for researchers. However, no bibliometric analysis related to LBP self‐efficacy has been performed to date. The purpose of this study was to conduct and explore the current state of research in LBP self‐efficacy from 1980 to 2021, by using bibliometric analysis and scientific mapping. Methods: Raw data were selected from the Web of Science (WOS) database, relevant literature on LBP self‐efficacy was retrieved, and data were de‐duplicated and cleaned. Excel was used for data processing. CiteSpace 5.8.R3 was used for bibliometric analysis and scientific mapping in publications and country, institution, journals, authors, references, and keywords. Statistical analysis was performed using IBM SPSS 25.0. Results: There were 822 references included. For this period, the total publication numbers were increased. A total of 103 regions had researchers in this area; the United States was the country with the largest volume of research. There were 94 disciplines, mainly in neuroscience. More research is likely to burst and develop quickly in general and internal medicine in the future. Spine was the most recognized journal. Cognitive‐behavioral manifestations and older adults with LBP might be the frontiers and trends. Conclusion: The volume of literature on LBP self‐efficacy has increased linearly over the past 41 years and will continue to increase. The field of study has become more refined. This bibliometric analysis provides valuable support for future directions and research trends in LBP self‐efficacy.